Gene variants in four pedigrees with hereditary coagulation factor XI deficiency and one novel mutation identification. Issue 2 (March 2020) - Lin, Fen; Weng, Miao-Shan; Wu, Jiao-Ren; Fang, Sen-Hai; Yang, Li-Ye
Abstract : N/A: Coagulation factor XI (FXI) deficiency is a bleeding disorder with unpredictable severity. Patients with this condition usually suffer bleeding manifestations after trauma or surgery and are poorly correlated with plasma FXI activity (FXI:C). In the current study, we examined and identified the phenotype and genotype in four unrelated probands and their 32 relatives with hereditary FXI deficiency. The probands with severely reduced FXI:C but bleeding symptoms were only found in two probands. Mutation analysis showed that all the probands were FXI homozygous mutation or compound heterozygous mutation. Five mutations were identified including three nonsense mutations c.841C>T (p.Gln263X), c.1107C>A (p.Tyr351X) and c.1033A>T (p.Lys327X), respectively, one frameshift mutation c.1325delT (p.Leu424CysfsX8), and one splicing mutation c.326-1G>A. c.1033A>T (p. Lys327X), a novel mutation which lead to a premature stop codon at amino acid position 327, it may have an influence on protein characteristics and cause the corresponding disease.